TorakochirurgiaEvaluation of systemic inflammatory response to pulmonary resection for NSCLC based on serum selectin concentration - Świniarska, Joanna; Kowalewski, Janusz; Żekanowska, Ewa (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Introduction: Inflammatory response is a key factor in carcinogenesis. Selectins are directly involved in this response, and indirectly in thrombosis and cancer progression, but the influence of pulmonary resection on serum selectin levels is not clearly defined so far. Aim: The aim of the study was to assess the influence of pulmonary resection for lung cancer on selectin expression. Histological type of cancer, stage of the disease and duration of surgery were taken into consideration in particular. Material and Methods: A prospective study was carried out on a group of 21 patients operated on for NSCLC. Seventeen of them underwent lobectomy and four pneumonectomy. In all of them systematic lymph node dissection was performed. Antithrombotic prophylaxis was covered by physical methods and by subcutaneous injection of low molecular heparin. The control group consisted of 39 healthy volunteers. The human tests of sP selectin, sL selectin and sE selectin, Instant ELISA Bender MedSystem Diagnostics GmbH, were used to measure the level of particular selectins in venous blood. The statistical analysis was based on Mann-Whitney U-test and Friedman test. Results: The levels of particular selectins were similar in the control group and in the study group before surgery. Histological type, stage of NSCLC and duration of surgical procedure were of no influence on the level of selectins. However, a significant decrease of L selectin on the first postoperative day and E selectin on the seventh postoperative day was measured in the study group. Conclusions: 1. There is no significant inflammatory response in patients with pathological stage I and II NSCLC. 2. Despite the extensive surgical procedure antithrombotic prophylaxis reduces the strong inflammatory response in which selectins are involved.